Principal Strategies for Developing an Organizational Culture in Education Management - Muhammad Ilham (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
Within the context of a school, organizational culture refers to the values and beliefs that form the basis of the school's identity and define the school's character. Excellent schools appreciate having excellent school leaders on staff. When a good administrator can help a school improve its organizational culture in order to provide a high-quality education to its students, this study makes use of library resources. Scientific books, research papers, scientific essays, theses, dissertations, regulations, yearbooks, and encyclopedias all serve as data sources. The data will be processed in stages, beginning with data reduction (data reduction), followed by data visualization (data visualization), and finally by generating conclusions/verification. The following methods can be used to carry out the principal's plan: (1) Enhancing educational services, beginning with intra- and extracurricular learning activities. (2) Rather of methodically developing actions and policies for monitoring long-term school performance through activities, the principal may adopt a management plan. (3) The principal must pay particular attention to the corporate culture's components